The mediating role of job satisfaction on the relationship between work-life balance and female employee performance influenced by burnout - Apriliani, Tri Rizki; Mukhsin, Moh. (International Journal of Applied Finance and Business Studies, 2024)
The importance of human resources among effective management systems. Human resource management in an organisation has become one of an agency's most essential functions and factors. This study aims to test and analyse the variables that affect employee performance, including work-life balance and burnout through job satisfaction, to develop a theoretical basis and research model. This study uses an associative descriptive quantitative method with a population and sample of 77 respondents with total/saturated technicality who are female employees in 29 sub-districts of Serang Regency. Questionnaire answers were measured using an interval scale of strongly disagree 1 - 10 strongly agree. Data were analysed with the help of SmartPLS Version 4.0 software. The results showed. Statistically, work-life balance can significantly affect employee performance; burnout can dramatically affect job satisfaction; work-life balance can substantially affect job satisfaction; job satisfaction can significantly affect employee performance, and job satisfaction can mediate the effect of work-life balance on employee performance; job satisfaction can be characterised as partial mediation. This research is expected to make a theoretical contribution to the literature in this context, especially in the context of human resource management